Tissue-infiltrating neutrophils represent the main source of IL-23 in the colon of patients with IBD. Issue 10 (9th July 2015) - Kvedaraite, Egle; Lourda, Magda; Ideström, Maja; Chen, Puran; Olsson-Åkefeldt, Selma; Forkel, Marianne; Gavhed, Désirée; Lindforss, Ulrik; Mjösberg, Jenny; Henter, Jan-Inge; Svensson, Mattias
Abstract : Objective: In IBD, interleukin-23 (IL-23) and its receptor (IL-23R) are implicated in disease initiation and progression. Novel insight into which cells produce IL-23 at the site of inflammation at an early stage of IBD will promote the development of new tools for diagnosis, treatment and patient monitoring. We examined the cellular source of IL-23 in colon tissue of untreated newly diagnosed paediatric patients with IBD. Design: Colon tissues from IBD and non-IBD patients were analysed by quantitative real-time PCR (qPCR), immunofluorescence confocal microscopy and flow cytometry after appropriate sample preparation. Blood samples from IBD and non-IBD patients and healthy controls were analysed using flow cytometry and qPCR. Results: We discovered that tissue-infiltrating neutrophils were the main source of IL-23 in the colon of paediatric patients with IBD, while IL-23 + human leucocyte antigen-DR + or IL-23 + CD14 + cells were scarce or non-detectable, respectively. The colonic IL-23 + neutrophils expressed C-X-C motif (CXC)R1 and CXCR2, receptors for the CXC ligand 8 (CXCL8) chemokine family, and a corresponding CXCR1 + CXCR2 + IL-23 + subpopulation of neutrophils was also identified in the blood of both patients with IBD and healthy individuals. However, CXCL8-family chemokines were only elevated in colon tissue from patients with IBD. Conclusions: This study provides the first evidence of CXCR1 + CXCR2 + IL-23-producing neutrophils that infiltrate and accumulate in inflamed colon tissue of patients with IBD. Thus, this novel source of IL-23 may play a key role in disease progression and will be important to take into consideration in the development of future strategies to monitor, treat and prevent IBD.